(untitled) (International journal of medical sciences, 2026)
The digestive system is one of the most complex and essential functions of the human body, including the processes of food intake, digestion, absorption, and waste elimination. This article analyzes the relationship between the digestive system and the central nervous system, reflex mechanisms, the enteric nervous system (ENS), and its interaction with gastrointestinal microbiota, based on modern scientific approaches. The research findings reveal the complex and integrated regulatory mechanisms of digestion and consider the role of stress, emotional state, and microbiota.